Nossa escola fechou, agora o quê fazer? Análise da política de fechamento das escolas do campo em conceição do tocantins - MARINHO, Iolanda Gonçalvas (Universidade Federal do Tocantins, 2025)
The objective of this study was: to analyze how political intentions present in the closing of the 21 (twenty-one) rural schools in the municipality of Conceição do Tocantins (TO). In this way, firstly, the concepts of the Field are contextualized in their known, historical and legal aspects. Next, a mapping of the real reasons for the closing of schools that were received in the municipality of Conceição (TO) is presented, due to the closing of schools with regard to the teaching-learning process in the region. As a methodology, a field study was carried out, with a descriptive character and a quantitative approach, through field survey and as a method of primary data collection: observation and interview; and secondary data obtained through the analysis of documents cited in other studies and authors that were still related to the topic, such as Caldart (2012) and Molina (2011). This data processing was performed from the interpretation, and inferences. Finally, the results revealed by the municipality of the schools do not show the denial of the right to education in the environment in which they live. So, the educational rights conquered end up being violated by the public in the process of mobilization and organization of rural communities. Thus, it is expected that this work will contribute to future readers, bring a new vision in the face of the scenario of closing rural schools. It is clear to think about quality that favors the stay of these subjects in the countryside and, in this way, an education.